EFEKTIVITAS PENAGIHAN PAJAK AKTIF DENGAN SURAT TEGURAN DAN SURAT PAKSA DALAM UPAYA OPTIMALISASI PENERIMAAN PAJAK (STUDI KASUS PADA KANTOR PELAYANAN PAJAK MADYA MALANG) - Purnawardhani, Restika (Jurnal Mahasiswa Perpajakan, 2015)
The purposes of this research are to determine the effectiveness of active tax collection on the Reprimand Letter and Forced Letter and their contribution towards optimize the tax revenues at Kantor Pelayanan Pajak Madya Malang. Those were conducted on the basis of the presence of the tax which is still owed to the state as shown in the realization of the State Budget fluctuating in three years period from 2011 to 2013. Those are also apparent in tax revenue at Kantor Pelayanan Pajak Madya Malang which doesn’t reach the set targets yet. Therefore, the state gives responsibility to the tax authorities to act as a law enforcement agent in the field of taxation, include a tax collection action. With the act of tax collection, especially active tax collection, it is expected that the taxpayer or tax insurer pay of the tax debt, so that the optimal tax revenue can be achieved. As a first step is to implement an active tax collection, Tax Bailiffs convey the Reprimand Letter that can be followed by Forced Letter for increasing taxpayer compliances. Keyword: Effectiveness, Active Tax Collection, Reprimand Letter, Force Letter, Tax Revenue